Extracellular HSP90 Machineries Build Tumor Microenvironment and Boost Cancer Progression - Poggio, Pietro; Sorge, Matteo; Seclì, Laura; Brancaccio, Mara (Frontiers in Cell and Developmental Biology, 2021)
HSP90 is released by cancer cells in the tumor microenvironment where it associates with different co-chaperones generating complexes with specific functions, ranging from folding and activation of extracellular clients to the stimulation of cell surface receptors. Emerging data indicate that these functions are essential for tumor growth and progression. The understanding of the exact composition of extracellular HSP90 complexes and the molecular mechanisms at the basis of their functions in the tumor microenvironment may represent the first step to design innovative diagnostic tools and new effective therapies. Here we review the impact of extracellular HSP90 complexes on cancer cell signaling and behavior.